COLONIZATION OF MANGROVE FOREST AT ABANDONED SHRIMP-POND OF SEGARA ANAKAN-CILACAP - Tjut Sugandawaty Djohan (Universitas Gadjah Mada, 2014)
During the 1996 to 1997, large areas of mangrove forest in the Segara Anakan were cleared and converted into intensive shrimp-ponds. After one to two years, these shrimp-ponds failed and were abandoned. These abandoned ponds created large gap areas and canopy gaps, which were colonized by mangrove shrub and liana. The Segara Anakan mangrove also experienced heavy siltation, and there were tree cuttings from the remnant of the mangrove trees. This research aimed to study the colonization of mangrove vegetation at the abandoned-shrimp pond. Vegetation data were collected using rectangular plots of 25 m x 25 m with 4 replicates. The water qualities were also studied. The results revealed that the mangrove forests were composed of two layers: canopy tree and floor-vegetation. The gap areas triggered the pioneer species of mangrove shrubs and liana, Acanthus ilicifolius and Derris heterophylla, to colonize and dominate 100% of the mangrove forest floor. The mangrove trees consisted of natural and planted tree species. The natural trees were Sonneratia alba, Avicennia alba, and saplings of Aegiceras corniculatum, which varied between 56 – 136, 4, and 4 individuals per ha, respectively. The planted trees were Rhizophora apiculata, which amounted to 4 – 12 individuals per ha, at the island of the ponds. These trees and saplings were entangled by the liana mangrove, which disturbed their growth. The A. ilicifolius and D. heterophylla prevented the mangrove tree propagules to grow, and they colonized and characterized those abandoned shrimp-ponds, which threatened the Segara Anakan mangrove ecosystem.